2019
DOI: 10.1111/geb.12985
|View full text |Cite
|
Sign up to set email alerts
|

Different determinants of radiation use efficiency in cold and temperate forests

Abstract: Aim To verify which vegetation and environmental factors are the most important in determining the spatial and temporal variability of average and maximum values of radiation use efficiency (RUEann and RUEmax, respectively) of cold and temperate forests. Location Forty‐eight cold and temperate forests distributed across the Northern Hemisphere. Major taxa studied Evergreen and deciduous trees. Time period 2000–2011. Methods We analysed the impact of 17 factors as potential determinants of mean RUE (at 8 days i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 52 publications
4
13
0
Order By: Relevance
“…We found that higher temperature was associated with higher LUE mostly in northern middle to high latitudes (Figures S3a and S3b), which was consistent with previous reports using site‐scale observations over this region (Balzarolo et al, 2019; Kergoat et al, 2008; Schwalm et al, 2006). In the tropics, higher temperature either had little or negative influence on LUE (Figures S3a and S3b).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We found that higher temperature was associated with higher LUE mostly in northern middle to high latitudes (Figures S3a and S3b), which was consistent with previous reports using site‐scale observations over this region (Balzarolo et al, 2019; Kergoat et al, 2008; Schwalm et al, 2006). In the tropics, higher temperature either had little or negative influence on LUE (Figures S3a and S3b).…”
Section: Discussionsupporting
confidence: 92%
“…As a crucial parameter for terrestrial carbon cycle, identifying the response of LUE to climate variability remains a critical challenge in understanding responses of vegetation photosynthesis to climate change and predicting future carbon cycle-climate interactions. It was clear that higher precipitation was correlated with higher LUE globally (Figures 4, S3c, and S3d), which was broadly consistent with recent studies based on a few site-scale observations (Balzarolo et al, 2019;Garbulsky et al, 2010). The influence of precipitation on LUE might come from direct pathways such as affecting the water supply to regulate plant water uptake (e.g., Chaitanya et al, 2003;Stocker et al, 2018;Zhang et al, 2015), or through indirect pathways such as altering the atmospheric water demand that might regulate the stomata (e.g., Akmal & Janssens, 2004;Waring et al, 2016).…”
Section: Response Of Lue To Climate Variabilitysupporting
confidence: 90%
See 1 more Smart Citation
“…On the other hand, global evapotranspiration and soil moisture data sets should be improved. Second, while the lack of high-quality global maps of C4 vegetation fraction and soil nutrition content limits the efficiency of ε max mapping (Waring et al, 2010), it has been recognized that the maximum LUE will vary annually, e.g., due to the rising atmospheric CO 2 (CO 2 fertilization effect), nitrogen deposition (Balzarolo et al, 2019;De Kauwe et al, 2016;He et al, 2017), land use changes and forest age increases (King et al, 2011;Landsberg & Waring, 1997), and may even fluctuate within a year due to the seasonal variations in vegetation cover and canopy structure (Kanako et al, 2014;Li et al, 2012;Lin et al, 2017). Accordingly, both the spatial and temporal variations in ε max need further explorations.…”
Section: A Potential Methods For Unified Global Lue Modelingmentioning
confidence: 99%
“…Indeed, GPP saturates at high APAR, while SIF keeps increasing as APAR increases, leading to a hyperbolic relationship between SIF and GPP at the instantaneous timescale (Damm et al, 2015;Gu et al, 2019). This hyperbolic-shaped relationship is less apparent over longer timescales, when variability in SIF and GPP is dominated seasonal variations in canopy structure, as estimated with the Leaf Area Index (LAI), whose effects are present in both SIF and GPP signals (Lu et al, 2018;Balzarolo et al, 2019;Dechant et al, 2020). Thus, the GPP:SIF correlation becomes more linear and relatively less sensitive to faster variations in the environmental drivers and plant physiological stress.…”
Section: Introductionmentioning
confidence: 99%